Analisis Pendekatan Konstruktivisme dalam Meningkatkan Pemahaman dan Penghayatan Nilai-Nilai Pendidikan Agama Islam - Ramadhannita, Retno Dwi (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
Islamic Religious Education carries significant responsibility in instilling religious values. The achievement of national education goals and the objectives of Islamic Religious Education greatly depend on the learning process. This research employs a qualitative approach based on descriptive analysis. The aim of this research is to discuss the analysis of how the constructivist approach can be applied to enhance students' understanding and appreciation of religious values. The findings of this study indicate that through the constructivist approach and its supportive teaching strategies, it is expected that students can improve their understanding and appreciation of religious values. The development of teaching approaches and models should ideally lead to the realization of the objectives of Islamic Religious Education subjects in terms of understanding and appreciating these values.